1991
DOI: 10.1111/j.1749-6632.1991.tb51576.x
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive Predictions of Outcome in Closed Head‐Injured Patients

Abstract: A comprehensive diagnostic evaluation was administered to 162 closed head-injured patients within 1 to 21 days (mean, 7.5 days) after injury. Each evaluation consisted of (1) power spectral analyses of electroencephalogram (EEG) recorded from 19 scalp locations referenced to age-matched norms, (2) brainstem auditory evoked potentials, (3) computed tomography (CT)-scan, and (4) Glasgow Coma Score (GCS) at time of admission (GCS-A) and at time of EEG test (GCS-T). Functional outcome at one year following injury … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
57
0
6

Year Published

1995
1995
2015
2015

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 95 publications
(67 citation statements)
references
References 30 publications
4
57
0
6
Order By: Relevance
“…59 qEEG studies have shown discriminant accuracy as high as 95.67% in the detection of mild head injury, 60 and >75.8% accuracy in the prediction of outcome one year after injury. 61 These findings have been confirmed by recent studies. [62][63][64][65] Persons with major depression can be differentiated from normal controls with a specificity of 91.3% and sensitivity of 91.3%.…”
supporting
confidence: 89%
“…59 qEEG studies have shown discriminant accuracy as high as 95.67% in the detection of mild head injury, 60 and >75.8% accuracy in the prediction of outcome one year after injury. 61 These findings have been confirmed by recent studies. [62][63][64][65] Persons with major depression can be differentiated from normal controls with a specificity of 91.3% and sensitivity of 91.3%.…”
supporting
confidence: 89%
“…300,309,314 These observations drove the development of combinations of qEEG findings that are used to generate statistical discriminant functions with which to diagnose TBI and in particular, mTBI. 274,275,[310][311][312][313] Substantial controversy remains regarding the products of these efforts. 269,282,291,314,317 The most widely known of the qEEG discriminant functions was developed by Thatcher and colleagues based on frontal and frontaltemporal coherence increases and phase decreases, decreased anteroposterior power differences, and reduced posterior cortical alpha power, among TBI subjects, compared with the healthy comparison subjects.…”
Section: Quantitative Electroencephalographymentioning
confidence: 99%
“…It is proposed that coherence provides an index of the integrity of inter-regional networks and communication between cortical areas, as well as with subcortical structures (e.g., thalamus and basal ganglia) that mediate this connectivity (Davey, Victor, & Schiff, 2000;Nunez, Wingeier, & Silberstein, 2001). Therefore, EEG coherence may serve as a better prognostic indicator for recovery after brain injury than power spectral analysis (Thatcher et al, 1991). Kane and colleagues (1998) found a significant reduction of the mean interhemispheric coherence of the EEG for all regions in comatose patients compared to normal healthy control subjects.…”
Section: Eeg In the Vegetative Statementioning
confidence: 99%